Analisis Keputusan Pembelian yang dilihat dari Harga, Kualitas Pelayanan dan Promosi pada Pasar Tradisional dan Toko Swalayan - Sinollah; Fenti Wulandari (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2023)
The background of this research is because the traditional market and Toko Kita have decreased in the number of consumers, the longer the market is getting quieter so the authors want to know whether price, service quality and promotion affect purchasing decisions at traditional markets and Toko Kita in Pringu Village. Methods of data collection using questionnaires, interviews, observation and documentation. The population used are traders and visitors at traditional markets and at